Efektivitas Sistem Disiplin Kerja Pada PT. Ravana Jaya - Nabillah, Putri Sofiyana; Amalina Rizqi, Maulidyah (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
In an increasingly competitive business world, as a growing construction company, PT Ravana Jaya does not easily maintain high work discipline among its employees. This study aims to analyze the effectiveness of the manual attendance system implemented at PT Ravana Jaya and its impact on work discipline and employee productivity. The research method used is a descriptive qualitative approach, with data collection through interviews and direct observation. The results of this study show that the effectiveness of the work discipline system is greatly influenced by the enforcement of regulations and the integration of various other aspects. Manual attendance systems lead to inaccuracies in attendance data, which negatively impacts the sanctions applied and employees' perceptions of fairness in the workplace. In addition, several operational obstacles were found, such as the risk of data loss and the inability of the fingerprint system to monitor employee behavior after attendance. This study recommends the implementation of a more efficient and structured digital attendance system to improve data accuracy, work discipline, and employee satisfaction.